An Experienced Chinese Teacher’s Strategies In Teaching Mathematics: Translation of Quadratic Functions - Xingfeng Huang; Jinglei Yang; Bingxing Tang; Lingmei Gong; Zhong Tian (SEAMEO Regional Centre for QITEP in Mathematics, 2012)
The study selected the topic of translation of quadratic functions. In order to explore some effective instructional strategies to help students understand this topic, an experienced teacher was chosen for a case study. Based on lesson observation and semi-structure interviews, this study found that the teacher employed various strategies to facilitate students understanding of translations of quadratic functions.